To simplify the expression \((7 - \sqrt{64}) + (6 + 3i)\), we will first simplify \(\sqrt{64}\).
Since \(\sqrt{64} = 8\), we can substitute this into the expression:
\[ 7 - \sqrt{64} = 7 - 8 = -1 \]
Now we will rewrite the original expression:
\[ (-1) + (6 + 3i) = -1 + 6 + 3i \]
Now, combine the real parts:
\[ (-1 + 6) + 3i = 5 + 3i \]
So the simplified expression is:
\[ 5 + 3i \]
None of the provided options directly mentioned \(5 + 3i\). If there was an error in recognizing the calculation, the correct answer based on options given does not appear to be present.